ESTIMATION OF SEASONAL VERTICALLY INTEGRATED PRIMARY PRODUCTIVITY IN AMBON BAY USING THE DEPTH-RESOLVED, TIME-INTEGRATED PRODUCTION MODEL - Basit, Abdul (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2012)
Seasonal vertically integrated primary productivity (IPP) in eight stations of Inner Ambon Bay (IAB) and ninestations of Outer Ambon Bay (OAB) was estimated using the depth-resolved, time-integrated production model andvertical-a distribution model which was mainly dependent on chlorophyll-a profile. The profile was modeled as Gaussfunction in which its parameters were determined by minimizing the difference between the model and the averageof in situ chlorophyll-a concentration from 2008 to 2012. The data was collected by UPT BKBL-LIPI Ambonduring monitoring program in Ambon Bay. Based on this model, the results showed that the primary productivityduring the southeast monsoon was to some degree higher than that of other seasons. The main factors causing the higherIPP in this season were upwelling phenomenon and high rainfall intensity. From the results, it could be concludedthat run-off gave more impacts in IAB than in OAB while upwelling in Banda Sea affected the IPP more in OABthan that in IAB. Then, the existence of the sill located between IAB and OAB inhibited the mixing of IAB andOAB waters so that the levels of IPP and chlorophyll-a concentration in IAB were higher than that of in the OAB.